Associations of Vitamin B-6 status and Regional Brain Volumetric Measures in the Boston Puerto Rican Health Study. (14th June 2022) - Bigornia, Sherman; Guan, Yi; Ebrahimzadeh, Amir; Scott, Tammy; Garelnabi, Mahdi; Zhang, Xiyuan; Palacios, Natalia; Koo, Bang-Bon; Bhadelia, Rafeeque; Tucker, Katherine
Abstract: Objectives: We quantified the associations of circulating vitamin B-6 concentration with regional brain volumes among Puerto Rican adults. In addition, associations with plasma vitamins B-12 and folate were investigated. Methods: Data are from the Boston Puerto Rican Health Study (n = 1499), where a subset of participants from the original cohort volunteered for T1-weighted MRI brain scans (n = 193) (78% female and aged 55 ± 7 y at baseline) approximately 13 years from the baseline visit. Circulating B-6 (pyridoxal 5′-phosphate, PLP), folate, and B-12 were measured from fasting blood samples collected at baseline and ∼2 and 5 y from baseline. Mean concentrations of these B vitamins were calculated for participants with blood samples from at least 2 of the 3 visits (baseline, 2-y, and 5-y). Whole MRI brain volumetric measures (of cortical and subcortical grey matter) were quantified using the FreeSurfer processing pipeline. Volumetric measurements included the frontal, parietal, temporal, and occipital lobes, cingulate gyrus, thalamus, caudate nucleus, putamen, hippocampus, amygdala, cerebellar white matter, and cerebellar cortex. Multivariable linear regression was used to examine associations between mean circulating B-6 and z score transformed regional brain volumes at 13-y. Secondary exposures were circulating folate and B-12 concentrations. A log transformation was applied to B vitamin concentrations. Models were adjusted for age, sex, BMI, smoking status, and intracranial volume. Results: Mean circulating PLP, folate, and B-12 were 64.5 ± 52 nmol/L, 19.3 ± 7.1 ng/mL, and 558 ± 242 pg/mL, respectively. We observed null associations between PLP and 13-y brain volumetric measures. Conversely, greater vitamin B-12 concentration was associated with greater parietal [β = 0.49 (95% CI: 0.02, 0.96), P = 0.04], putamen [0.88 (0.221, 1.54), P = 0.009], and cerebellar white matter volumes [0.71 (0.08, 1.33), P = 0.02]. Folate was positively associated with thalamus measurements [1.06 (0.34, 1.78), P = 0.004]. Results remained similar after accounting for a history of cardiovascular disease and type 2 diabetes. Conclusions: These results suggest that, among older Puerto Rican adults, greater vitamin B-12 and folate, but not B-6, status may be related to greater volumetric measures of select brain structures. Funding Sources: National Institute on Aging.